Botswana : Technical Assistance Report-Banking Sector Safety Net and Crisis Management. (IMF Staff Country Reports; Country Report, 2017)
This Technical Assistance Report evaluates the banking sector safety net and crisis management in Botswana. The current legislative framework guiding bank resolution and financial sector crisis management is weak, and the authorities have embarked on a revision. The Bank of Botswana lacks some of the legal powers required for implementing corrective action for banks that are in breach of prudential requirements or are conducting business in an unsound or unsafe manner. Key elements for a corrective action framework, including a contingency plan for dealing with weak banks and guidance on indicative remedial measures based on well-defined triggers, are also lacking, and major amendments to the legal framework are needed.